Scientific biography of stanley mandelstam: 1981-2016 - Berkovits, Nathan [UNESP] (World Scientific Publishing, 2017)
In this contribution to the memorial volume, I will review Stanley Mandelstam's work after 1980 and concentrate on his powerful application of light-cone gauge methods in super-Yang-Mills theory and superstring theory.